2020
DOI: 10.3390/socsci9070116
|View full text |Cite
|
Sign up to set email alerts
|

Help and Solidarity Interactions in Interactive Groups: A Case Study with Roma and Immigrant Preschoolers

Abstract: Peer interactions in early childhood education play a key role in establishing the first structures of social relationships and foundations for future development. Engaging in social exchanges with different people enriches children’s concurrent and future learning opportunities. Building on the importance of diversifying interactions, interactive groups (IGs) are a specific dialogue-based classroom organization format that creates an inclusive learning environment by allocating students to small heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In this case, Roma women, professionals, and workers of the civic association were in constant dialogue during the pandemic. This resulted in the application of extended learning time and interactive groups [34,35]-two of the successful educational actions identified by the scientific literature. The participants explained the benefits these actions had on their children.…”
Section: Positive Results From the Combination Of Co-creation And App...mentioning
confidence: 99%
“…In this case, Roma women, professionals, and workers of the civic association were in constant dialogue during the pandemic. This resulted in the application of extended learning time and interactive groups [34,35]-two of the successful educational actions identified by the scientific literature. The participants explained the benefits these actions had on their children.…”
Section: Positive Results From the Combination Of Co-creation And App...mentioning
confidence: 99%
“…It has been shown that SEPs enable students to express their own opinions and emotions in a manner that enhances cohesion among students, fosters friendship among students (Aubert et al, 2017 ; Duque et al, 2020 ) and creates bonds of solidarity and mutual help (Villardon-Gallego et al, 2018 ). A study found that gatherings were associated with prosocial behavior among students (Khalfaoui et al, 2020 ). According to the authors, preschoolers can engage in flexible interactions by arranging the classroom dialogically, which promotes dialogic learning.…”
Section: Resultsmentioning
confidence: 99%
“…PE that integrates inclusive, technology-driven, and learner-centered strategies not only enhances students' physical skill acquisition but also contributes to their overall development. Aside from laying the foundation for a healthier future, these practices promote life skills such as self-confidence, determination, and an appreciation of PA for a lifetime (Wright and Burton, 2008 ; Beaulac et al, 2011 ; Connolly et al, 2011 ; Diez et al, 2011 ; Karasimopoulou et al, 2012 ; Noggle et al, 2012 ; Sifers and Shea, 2013 ; Standage et al, 2013 ; Valls and Kyriakides, 2013 ; Flecha and Soler, 2014 ; Gomez et al, 2014 ; Padros, 2014 ; Aubert, 2015 ; Garcia-Carrion, 2015 ; Grace, 2015 ; Kall et al, 2015 ; Molina Roldan, 2015 ; Costigan et al, 2016 ; Hankonen et al, 2016 ; Lubans et al, 2016 ; Smedegaard et al, 2016 ; Aubert et al, 2017 ; Bakir et al, 2017 ; Gül et al, 2017 ; Ha et al, 2017 ; Ho et al, 2017 ; McNamee et al, 2017 ; Puigdellivol et al, 2017 ; Capllonch Bujosa et al, 2018 ; Garcia-Carrion et al, 2018 , 2020a , b ; Hignett et al, 2018 ; Valero et al, 2018 ; Villardon-Gallego et al, 2018 ; Lopez de Aguileta, 2019 ; Luna et al, 2019 ; Slee and Allan, 2019 ; Villarejo-Carballido et al, 2019 ; Diez-Palomar et al, 2020 ; Huescar Hernandez et al, 2020 ; Khalfaoui et al, 2020 ; Lopez de Aguileta et al, 2020 ; Roca et al, 2020 ; Zubiri-Esnaola et al, 2020 ). In light of PE's ongoing evolution, it is crucial to understand and optimize this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our results show that solidarity is a characteristic of the interactive learning environment studied, connected to the improvements achieved. Previous research has highlighted solidarity as one main component of interactive learning environments such as dialogic literary gatherings and interactive groups (Pulido-Rodríguez et al, 2015 ; Khalfaoui et al, 2020 ), and adult education has been identified as a context of collective action, mobilisation and solidarity leading to greater equity and inclusion (Heidemann, 2020 ; Smythe et al, 2021 ). Drawing on solidarity can contribute to approaching the right to quality inclusive education for people with disabilities at all levels and lifelong learning, as recognised in the Convention on the Rights of Persons with Disabilities (UN, 2006 ).…”
Section: Discussionmentioning
confidence: 99%